Antimicrobial Susceptibility Pattern of Bacterial Isolates from Wound Infection - Nahar, S Gul; Hasan, M Bulbul; Ali, M Nawshad; Khatun, Mst Rokeya; Khanam, K (TAJ: Journal of Teachers Association, 2018)
Objective: The present study was done to see the antimicrobial susceptibility pattern of bacterial isolates from wound infection. Methods: Wound swabs collected from 150 patients of wound infection were cultured and microbial isolates identified using standard methods. Antimicrobial susceptibility testing was done on bacterial isolates by Modified Kirby Bauer method. Results: Of the 150 swabs 131 (87.4%) were culture positive for bacterial pathogens, while 19 (12.6%) were bacteriologically sterile showing an isolation rate of 87.4%. The predominant bacteria isolated from the infected wounds were Staphylococcus aureus 47 (32.4%) followed by Escherichia coli 29 (20%), Proteus species 23 (16%), Coagulase negative Staphylococci 21 (14.5%), Klebsiella pneumoniae 14 (10%) and Pseudomonas aeruginosa 11 (8%).In case of gram positive bacteria- rate of isolates resistant to ampicillin was 94%, followed by penicillin G, 86.8%, Tetracycline, 51.5%. In case of gram negative bacteria- rate of isolates resistant to ampicillin was 96%, followed by cephalothin, 92.4%, Tetracycline, 74%. Conclusion: In antimicrobial susceptibility testing ampicillin, penicillin, cephalothin and tetracycline were the least effective. Gentamicin, norfloxacin, ciprofloxacin, vancomycin and amikacin were the most effective antibiotics. TAJ 2013; 26: 61-66